1989
DOI: 10.1002/jmr.300020105
|View full text |Cite
|
Sign up to set email alerts
|

The conformation of core oligosaccharides from Escherichia coli and Salmonella typhimurium lipopolysaccharides as predicted by semi‐empirical calculations

Abstract: The preferred conformation of the hexose and heptose regions of core saccharides from Enterobacteriaceae lipopolysaccharides was calculated. The Hard Sphere Exo Anomeric (HSEA) approach was used and the minimum energy conformation of the Salmonella typhimurium and Escherichia coli R1, R2, R3, R4 and K12 cores calculated. The results indicate that most of the cores are sterically crowded, with small degrees of freedom, and that the hexose and heptose parts form two separate regions. The core structures exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Moreover, conformational similarities in the outer core (hexose region) of Salmonella spp. and of E. coli Rl to R4 and K-12 LPS have been predicted by semiempirical calculations (29). These results are in line with our data which suggest that the outer core may contribute to the Ab binding surface.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, conformational similarities in the outer core (hexose region) of Salmonella spp. and of E. coli Rl to R4 and K-12 LPS have been predicted by semiempirical calculations (29). These results are in line with our data which suggest that the outer core may contribute to the Ab binding surface.…”
Section: Discussionsupporting
confidence: 92%
“…A unique binding site for the R2-specific antibody is not obvious from the structural formulas. From the calculated three-dimensional structure of the different core types [24], however, it appears that the branch-terminating a 1-6 galactose present in R2, Salmonel/a core, and K 12 may be in a different orientation in R2 and may therefore be the R2-specific epitope. It is of note that while most of the core-specific MAbs reacted in immunoblot only with unsubstituted core, the R2-specific MAb also reacted with a-substituted core, giving a ladder pattern in immunoblots.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesized mono‐, di‐ or trisaccharide could be used for this purpose. Alternatively, previous studies have demonstrated that the sugar composition has an influence on the conformation of the core OS (Jansson et al ., 1989; Bruse et al ., 1991). Thus, the loss of the GalNAc‐Gal II‐Gal I region might lead to a conformation that is less able to bind the toxins.…”
Section: Discussionmentioning
confidence: 99%